Simulating the Impact of Long-Term Care Prevention Among Older Japanese People on Healthcare Costs From 2020 to 2040 Using System Dynamics Modeling - Nishi, Nobuo; Ikeda, Nayu; Sugiyama, Takehiro; Kurotani, Kayo; Miyachi, Motohiko (Frontiers in Public Health, 2020)
Objectives: This study examined how healthcare costs might change by reducing long-term care needs among older Japanese people. Methods: A simulation model was constructed comprising two aging chains for independent and dependent people aged ≥65 years by sex. Changes in the base run from 2020 to 2040 were compared with those in two hypothetical scenarios: a 2% annual reduction in death rates (S1), and S1 plus a 2% annual reduction in the proportion of dependent people aged 65 years and in transition rates from the independent to dependent state for people aged ≥65 years (S2). Results: In the base run, the population increased by 13.0% for men and 11.3% for women, and the proportion of dependent people increased by 4.6% for men but decreased by 13.4% for women. The sum of medical and long-term care expenditure increased in the base run, S1, and S2 by 8.2, 27.4, and 16.4%, respectively, for men and women combined. Conclusions: Healthcare costs will increase as death rates fall, but the increase will be attenuated if the proportion of dependent people decreases.